Desenvolvimento da teoria da mente e da linguagem: como as crianças explicam desejos, intenções e crenças - Pellegrini, Rosimeire Aparecida Vicente (2015)
The skill development in understanding mental states wishes, intentions and beliefs has been studied by the name of Theory of Mind. It s at the early ages that children acquire the ability of understanding that other people have wishes, intentions and beliefs that can be different from theirs. The Theory of Mind is an important moment in the social cognitive development, because it allows us to explain and predict people s behavior, making interpersonal relationships easier. The objective of this research was to investigate how children attribute mental states of wishes, intentions and beliefs to stories characters and to analyse the given justifications in a way to verify the hypothesis of the relation between the language development and the theory of mind, focusing on the use of epistemic verbs (to know, to think, and to believe) and the ability to give coherent answers in the justifications of the theory of mind tasks. It was also the objective of this research to control the order effect in the application of the Scaling Tasks and to verify the relation to the age in mental states comprehension. 70 children in the age between 3 years old and 5 years and 11 months old from average and average high standard of living families who attended classes in a private school in São Caetano do Sul, a city in São Paulo took part of the study. A test of verbal level was done and seven Scaling Tasks were applied. The results showed that most of the children, when invited to justify their answers in the tasks of the theory of mind, reflected about their wrong answers and corrected themselves pointing out to the comprehension of the mental states. Regarding the variable order effect in the application of the Scale, it was noticed that some tasks which were considered more difficult by the literature were shown to be of easy comprehension to the participants of this research. It s important to emphasize that these results are preliminary and other studies involving a larger number of Brazilian kids are necessary to evaluate Scaling Tasks in the Theory of Mind. Regarding the difference in ages, the results agree with the literature, once the children tended to answer precociously to the tasks of wishes and tardily to the tasks of false belief. Another fact that also coincides with the former studies is the use of epistemic verbs by the children before the comprehension of mental verbs. These results support the hypothesis of a relation between the theory of mind and the language development